Study on the influence of the tectonic evolution of Shuangyashan Basin on gas occurrence and extraction in mines - Lan, Tianwei; Zhang, Zhijia; LE, QUY BAO; Liu, Yonghao; Wang, Shunxiang (Frontiers in Earth Science, 2023)
The formation and later evolution of coal-bearing basins in eastern Heilongjiang are controlled by multi-phase tectonic movements, and the Shuangyashan Basin is tectonically located at the southern end of the Sanjiang Basin in the northeast. The paper focuses on the regional geological and tectonic evolution of the Shuangyashan Basin and its influence on the gas occurrence law and extraction difficulty of the Jixian Coal Mine. The study determined that the gas occurrence of the mine in the Suibin-Jixian depression basin has regional aggregation and caprock sealing characteristics. The gas pressure and content of the 9# Coal Seam were measured in the underground test, and the results showed that the 9# coal seam is a hard-to-extract coal seam with low permeability. Aiming at the issue of hard-to-extract gas in 904 Working Face of 9# Coal Seam which is affected by depression basin and derived secondary tectonic conditions, numerical calculation and analysis of gas extraction effect of working face with different extraction parameters were carried out by COMSOL software, the results showed that: negative extraction pressure has less influence on gas extraction effect under basin conditions; when 113 mm diameter borehole is used for gas extraction, gas pressure decreases to 0.72 MPa; when the spacing of extraction borehole is 2 m, the gas pressure is reduced by 20%; when the coal seam permeability is increased by 10 times to more than 0.015 mD, the gas pressure is reduced by more than 50%. The optimized gas extraction scheme with 113 m diameter, 2 m borehole spacing, and 15 kPa negative pressure was proposed for the test working face, and combined with supercritical CO2 fracturing and permeability enhancement technology. Under underground measurement, the coal seam gas content was reduced by 39.7% compared to the original gas extraction scheme. It can be seen that the reasonable gas extraction scheme and coal seam pressure relief and permeability enhancement technology can significantly improve the gas extraction rate, and the extraction effect is remarkable.